2023
DOI: 10.1186/s12870-023-04173-3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of a flavanone 3-hydroxylase gene from citrus fruit reveals its crucial roles in anthocyanin accumulation

Abstract: Background Flavanone 3-hydroxylase (F3H), a key enzyme in the flavonoid biosynthetic pathway, plays an important role in the regulation of flavonols and anthocyanidins accumulation. Citrus fruit is a rich source of flavonoids with varied flavonoid compositions among different varieties. To date, the study on F3H is limited in citrus, and its roles in regulating flavonoid accumulation in citrus fruit are still unclear. Results In this study, we isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…A differential gene expression analysis between these clusters showed that numerous genes upregulated in cluster 6 (defined by an average log2 fold-change > 0.75 and an adjusted pvalue < 0.05) were involved in the light-capture phase of photosynthesis (such as LHCA4, psaK, CAB), along with genes in carotenoid (CRTISO 47 ) and chlorophyll (Chlorophyllide a oxygenase 48 ) biosynthesis pathways (Supplementary table 3). Conversely, genes DE in cluster 5 had broader functions in plant metabolism, including lipid biosynthesis (e.g., FAR1 49 , 13 FATB1 50 ), flavonoid biosynthesis (e.g., PAL 51 , FLS 52 ), sugar metabolism and transport (e.g., ERD6-like transporters, FBA5), and carbon metabolism (Rubisco small subunit 2; Supplementary table 3). These observations highlighted the temporal sequence from light capture, facilitating the downstream activation of the CBB cycle, eventually leading to sugar and broader plant metabolism.…”
Section: Cell Trajectory Inference Analysis Reconstructs a Cam 24-hou...mentioning
confidence: 99%
“…A differential gene expression analysis between these clusters showed that numerous genes upregulated in cluster 6 (defined by an average log2 fold-change > 0.75 and an adjusted pvalue < 0.05) were involved in the light-capture phase of photosynthesis (such as LHCA4, psaK, CAB), along with genes in carotenoid (CRTISO 47 ) and chlorophyll (Chlorophyllide a oxygenase 48 ) biosynthesis pathways (Supplementary table 3). Conversely, genes DE in cluster 5 had broader functions in plant metabolism, including lipid biosynthesis (e.g., FAR1 49 , 13 FATB1 50 ), flavonoid biosynthesis (e.g., PAL 51 , FLS 52 ), sugar metabolism and transport (e.g., ERD6-like transporters, FBA5), and carbon metabolism (Rubisco small subunit 2; Supplementary table 3). These observations highlighted the temporal sequence from light capture, facilitating the downstream activation of the CBB cycle, eventually leading to sugar and broader plant metabolism.…”
Section: Cell Trajectory Inference Analysis Reconstructs a Cam 24-hou...mentioning
confidence: 99%